The Influence of Content Marketing, Experiential Marketing and Electronic Word of Mouth (e-WOM) on The Ticket Purchase Decision for The Movie Better Off Dead Among Gen Z Consumers in Jabodetabek - Khilda Nur Uswah Akhsariah; Nadya Fadillah Fidhyallah; Daru Putri Kusumaningtyas (The Future of Education Journal, 2026)
The Indonesian film industry is experiencing rapid growth, marked by an increase in local film production and high audience interest. However, high-quality films do not always achieve commercial success, as shown by Better Off Dead, which received positive reviews but attracted relatively few viewers. This study aims to analyze the influence of content marketing, experiential marketing, and electronic word of mouth (e-WOM) on movie ticket purchase decisions among Gen Z consumers in Greater Jakarta. Using a quantitative explanatory approach, data were collected from 110 respondents through purposive sampling and analyzed using SPSS with multiple linear regression. The findings reveal that content marketing, experiential marketing, and e-WOM each have a positive and significant effect, both partially and simultaneously, on purchase decisions. Among these variables, e-WOM emerged as the most influential factor, highlighting the crucial role of online reviews, recommendations, and information on social media in shaping Gen Z consumers’ decisions. This study offers implications for the film industry to optimize content marketing strategies, create more personalized and memorable experiences for audiences, and foster positive e-WOM to increase movie ticket purchases.